Kutai Kartanegara LPPL 100.6 Fm Government Radio Communication Strategy in Maintaining Its Existence - Fahrezy, Mohammad Irgi Hafizh; Rohmah, Ainun Ni’matu; Sucipta, Johantan Alfando Wikandana; Kristian, Dony (CV. Publikasi Indonesia, 2025)
This study investigates the communication strategy of Kutai Kartanegara Government Radio as a Local Public Broadcasting Institution 100.6 FM in maintaining its existence. Against the backdrop of technological advances that have given rise to new media offering flexibility and fierce competition in the radio industry, this study aims to understand how radio broadcasting institutions maintain their existence amidst the presence of new media and competition between radio industries. The researcher used a descriptive qualitative research method with a Case Study approach through interviews, observations, and documentation. The results of the study indicate that Kutai Kartanegara Government Radio forms a structure, conducts surveys to improve the quality of broadcasting programs and adjusts to listener preferences, The planning stage involves setting clear goals for digital transformation, listener segmentation, content adjustment, In the implementation carried out displaying special programs, and interactive, in routine evaluations carried out to review the effectiveness of the program and see from the listener's response. reporting is made routinely and in writing and becomes the basis for future decision making. From the results of the discussion, it can be concluded that the communication strategy carried out by Kutai Kartanegara Government Radio applies the stages of communication strategy according to Hafied Cangara, namely research, planning, implementation, evaluation, and reporting and applies the Boundary Spanning Theory in several stages.